Fundamentals of rocket propulsion - Mishra, D. P. (Aerospace engineer) (CRC Press, 2017)
"The book follows a unified approach to present the basic principles of rocket propulsion in concise and lucid form. This textbook comprises of ten chapters ranging from brief introduction and elements of rocket propulsion, aerothermodynamics to solid, liquid and hybrid propellant rocket engines with chapter on electrical propulsion. Worked out examples are also provided at the end of chapter for understanding uncertainty analysis. This book is designed and developed as an introductory text on the fundamental aspects of rocket propulsion for both undergraduate and graduate students. It is also aimed towards practicing engineers in the field of space engineering. This comprehensive guide also provides adequate problems for audience to understand intricate aspects of rocket propulsion enabling them to design and develop rocket engines for peaceful purposes. Key Features:" Book presents an integrated approach including mechanics, modeling, manufacture and design of composite components including theory and practice." Exhaustive discussion on analysis and analytical methods for composite beams, columns and plates, and the basic procedure of the finite element method." Principles of composite manufacturing, common manufacturing methods and selection of manufacturing methods are presented in depth." Presents concept of design and composite design process, along with several representative design examples." Includes fully-solved examples with solutions manual and high quality illustrative figures"--Provided by publisher